EFFECTIVENESS OF ANTIVIRAL THERAPY OF CHRONIC VIRAL HEPATITIS C IN CHILDREN - A.S. Potapov; N.L. Pakhomovskaya; G.V. Volynets ("Paediatrician" Publishers LLC, 2009)
The article describes an efficacy of interferon alpha-2a (Roferon-A) in 69 children with chronic viral hepatitis C. The frequency of forming of initial and prolonged remission and the role of such factors as viral genotype, the level of viral load, terms of elimination of virus, the evidence of histological changes in liver's parenchyma in prognosis of remission and late relapse development was shown. Authors estimated the safety of the drug. Key words: children, chronic viral hepatitis C, interferon alpha-2a, treatment. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(6):101-105)